2013 IDSA Clinical Practice Guideline for Vaccination of the Immunocompromised Host. (4th December 2013) - Rubin, Lorry G.; Levin, Myron J.; Ljungman, Per; Davies, E. Graham; Avery, Robin; Tomblyn, Marcie; Bousvaros, Athos; Dhanireddy, Shireesha; Sung, Lillian; Keyserling, Harry; Kang, Insoo
Abstract: An international panel of experts prepared an evidenced-based guideline for vaccination of immunocompromised adults and children. These guidelines are intended for use by primary care and subspecialty providers who care for immunocompromised patients. Evidence was often limited. Areas that warrant future investigation are highlighted.